Effect of Lumbar Spine Manipulation on Asymptomatic Cyclist Sprint Performance and Hip Flexibility - Olson, Eric (J Chiropr Med, 2014)
OBJECTIVE: The purpose of this study was to measure the impact of midlumbar spinal manipulation on asymptomatic cyclist sprint performance and hip flexibility. METHODS: Twelve cyclists were equally randomized into an AB:BA crossover study design after baseline testing. Six participants were in the AB group, and 6 were in the BA group. The study involved 1 week of rest in between each of the 3 tested conditions: baseline testing (no intervention prior to testing), condition A (bilateral midlumbar spine manipulation prior to testing), and condition B (sham acupuncture prior to testing, as a control). Testing was blinded and involved a sit-and-reach test followed by a 0.5-km cycle ergometer sprint test against 4-kp resistance. Outcome measures were sit-and-reach distance, time to complete 0.5 km, maximum heart rate, and rating of perceived exertion. An additional 8 cyclists were recruited and used as a second set of controls that engaged in 3 testing sessions without any intervention to track test acclimation. An analysis of variance was used to compare dependent variables under each of the 3 conditions for the experimental group and control group #1, and a repeated-measures analysis of variance was used to analyze test acclimation in control group #2. RESULTS: Lumbar spine manipulation did not demonstrate statistically significant between-group changes in sit-and-reach (P = .765), 0.5-km sprint performance time (P = .877), maximum exercise heart rate (P = .944), or rating of perceived exertion (P = .875). CONCLUSIONS: The findings of this preliminary study showed that midlumbar spinal manipulation did not improve hip flexibility or cyclist power output of asymptomatic participants compared with an acupuncture sham and no-treatment control groups.